Recent Research and Development on Solar Energy Application Japan - Noguchi, Tetsuo (Annals of Arid Zone, 2016)
In the course of the next two years Japan will be investing about 874 million yen on R &D in the field of Solar Energy Utilization, with particular emphasis on solar thermal conversion, photovoltaic conversion, solar heating and cooling,hot water supply, solar furnaces and other aspects. The paper discusses Japanese efforts and achievements in these fields till 1975.